Medical image computing and computer-assisted intervention - MICCAI 2011 14th International Conference, Toronto, Canada, September 18-22, 2011, Proceedings, Part I - Fichtinger, Gabor; Martel, Anne; Peters, Terry (Lecture Notes in Computer Science, 2011)
The three-volume set LNCS 6891, 6892 and 6893 constitutes the refereed proceedings of the 14th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2011, held in Toronto, Canada, in September 2011. Based on rigorous peer reviews, the program committee carefully selected 251 revised papers from 819 submissions for presentation in three volumes. The first volume includes 86 papers organized in topical sections on robotics, localization and tracking and visualization, planning and image guidance, physical modeling and simulation, motion modeling and compensation, and segmentation and tracking in biological images.